2020
DOI: 10.1111/ans.15684
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival outcomes of undifferentiated embryonal sarcoma of the liver: a pooled analysis of 308 patients

Abstract: Background Treatment of undifferentiated embryonal sarcoma of the liver (UESL) is a great clinical challenge due to its rarity. This study aims to examine the long‐term survival of UESL patients after treatment using different therapeutic modalities. Methods A pooled analysis of individual data was performed on all UESL patients obtained from literature search (n = 307) and our institution (n = 1). Results The 5‐year overall survival rate of the 308 patients was 65.8%, 70% for partial hepatectomy group (n = 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(87 citation statements)
references
References 11 publications
3
82
2
Order By: Relevance
“…Multimodal therapy consisting of local resection or LT, and neoadjuvant multiagent chemotherapy to facilitate resection, results in survival rates of 65-75%. Several regimens have included alkylators, platinums, podophyllotoxins, anthracyclines, and topoisomerase I. inhibitors, among others [33,66]. There is less agreement about the optimal treatment of MRT.…”
Section: Chemotherapymentioning
confidence: 99%
“…Multimodal therapy consisting of local resection or LT, and neoadjuvant multiagent chemotherapy to facilitate resection, results in survival rates of 65-75%. Several regimens have included alkylators, platinums, podophyllotoxins, anthracyclines, and topoisomerase I. inhibitors, among others [33,66]. There is less agreement about the optimal treatment of MRT.…”
Section: Chemotherapymentioning
confidence: 99%
“…However, it may have better outcomes compared to angiosarcoma when surgically resected. A recent review article including 271 patients who received partial hepatectomy showed a 5-year survival rate of 70%[ 10 ]. The 5-year survival rate for the undifferentiated sarcoma group in our study was 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Walther et al [ 20 ] studied 3 patients who received LT and remained in clinical remission for a mean of 35 mo. Wu et al [ 10 ] showed 14 patients who received LT for hepatic undifferentiated sarcoma with a 5-year survival rate of 78.9%. When weighing the benefits of LT against the risks for the liver donor or the shortage of deceased donor, LT in hepatic undifferentiated sarcoma is still controversial and needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…2 Advances in management of these tumors including surgical resection, with or without liver transplantation, along with adjuvant high-dose alkylator-and anthracycline-based chemotherapy provides a curative outcome in the majority of cases. 1,[3][4][5][6][7] Although there is no universally accepted treatment, the systemic approach is generally similar to that of other soft tissue sarcomas. [3][4][5]7 Notably, a recent pooled analysis of UESL demonstrated a 5-year overall survival of 70% for those who were able to undergo surgical resection.…”
Section: Introductionmentioning
confidence: 99%